COST-EFFECTIVENESS OF OUTSOURCING LOCAL GOVERNMENT REVENUE COLLECTION IN TANZANIA: THE CASE OF KINONDONI AND MOROGORO MUNICIPAL COUNCILS - Mtasigazya, Paul (PEOPLE: International Journal of Social Sciences, 2018)
There is still lack of clarity regarding the question of whether outsourcing of revenue collection has led to cost saving in Tanzania. Against the backdrop of this question, this paper investigated cost-effectiveness of outsourcing revenue collection to establish whether cost-saving has been realized after outsourcing revenue collection by comparing with the costs incurred before outsourcing in Kinondoni and Morogoro Municipal Councils. The study adopted the case study research design and the methods of data collection were interviews and documentary review. The findings indicate that cost-saving was realized after outsourcing of property tax and guest house levy. This was because the tendering costs incurred after outsourcing were lower than the cost incurred on employing revenue collectors and stationary expenses before outsourcing. The findings support the theoretical framework guiding this study using the assumption of Transaction Cost Theory which assumes that in a transaction where integrity is adhered to, the transaction costs are likely to be reduced. Also, it can be observed that outsourcing increased the cost of collecting the public toilet fees in Kinondoni Municipal Council due to failure in monitoring the private companies. In view of the findings discussed, it is concluded that outsourcing revenue collection can result to saving cost when outsourcing is executed with integrity in Kinondoni and Morogoro Municipal Councils.